2017
DOI: 10.15376/biores.12.2.2792-2804
|View full text |Cite
|
Sign up to set email alerts
|

High-Yield Pulp from Brassica napus to Manufacture Packaging Paper

Abstract: The stalks that are left on the field after harvesting rapeseed crops could be used to make packaging grade paper. This work evaluates the suitability of mechanical and thermomechanical pulps from rapeseed stalks for papermaking, with a view to alleviating the limitations of recycled fluting. Their performance was compared to that of commercial fluting (recycled fluting) of the same basis weight, 100 g/m 2 , and to that of virgin pulps from pine wood. The thermomechanical pulp was refined to improve key mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…These treatments result in the isolation of the lignocellulosic fibers from the original biomass. In this context, the increase in the severity of the treatment leads to a reduction in the yield of the process, as well as a modification in the chemical composition of the resulting fibers [ 26 , 27 , 28 ]. According to the 12 Principles of Green Chemical Engineering, enunciated by Anastas and Zimmerman [ 29 ], the activity of scientists and engineers must converge in the design of new materials, products, processes, and systems that are beneficial to health and the environment.…”
Section: Introductionmentioning
confidence: 99%
“…These treatments result in the isolation of the lignocellulosic fibers from the original biomass. In this context, the increase in the severity of the treatment leads to a reduction in the yield of the process, as well as a modification in the chemical composition of the resulting fibers [ 26 , 27 , 28 ]. According to the 12 Principles of Green Chemical Engineering, enunciated by Anastas and Zimmerman [ 29 ], the activity of scientists and engineers must converge in the design of new materials, products, processes, and systems that are beneficial to health and the environment.…”
Section: Introductionmentioning
confidence: 99%
“…1b), the influence is barely noticeable. Similarly, the Brassica napus pulps studied by Aguado et al (2015) and Moral et al (2017) showed gradual variations in the tear rate when revolutions of the PFI mill were increased.…”
Section: Characterization Of Paper Sheetsmentioning
confidence: 74%
“…A total of four different pulps were used for paper production, as reflected in Table 3, together with their basic characterization. The reference pulp presented 41 °SR, a typical value for brown-line recycled pulps (Biricik and Atik 2012;Moral et al 2017). When this pulp was enzymatically refined, drainability was kept almost constant with no significant changes in fibers' morphology, since length was merely decreased from 844 to 768 µm.…”
Section: Recycled Pulp and Paper Characterizationmentioning
confidence: 99%